2022
DOI: 10.1177/14653125221099962
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s experiences of orthodontic retainers: A qualitative study

Abstract: Objective: To investigate young people’s experiences of retainers, the associated impact of retainers on their lives and their perceptions of what influences their own co-operation. Design: Qualitative, cross-sectional study. Setting: An orthodontic department in a UK dental hospital. Participants: Purposive sampling was used to recruit young people, aged 11–17 years, wearing a range of different types of retainers. Methods: Semi-structured interviews were conducted and transcribed. The resultant data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is shown in this study that plaque accumulation is increased in fixed types of retainers compared to removable ones, it also emerged that after the patients were strictly instructed on hygiene techniques and asked to improve dental hygiene habits (e.g., brushing three times a day with given standardized toothpastes and toothbrushes) the plaque scores dropped showing the major importance of correct oral hygiene protocols [11]. Removable retainers facilitate the oral hygiene procedures, but their effectiveness is solely dependent on the patient's motivation [21]. The study by Eroglu et al [11] recorded a statistically significant decrease of plaque level accumulation for all groups (VFR group and FR group) from the initial measurement that was taken after debonding to the last one taken at 13 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown in this study that plaque accumulation is increased in fixed types of retainers compared to removable ones, it also emerged that after the patients were strictly instructed on hygiene techniques and asked to improve dental hygiene habits (e.g., brushing three times a day with given standardized toothpastes and toothbrushes) the plaque scores dropped showing the major importance of correct oral hygiene protocols [11]. Removable retainers facilitate the oral hygiene procedures, but their effectiveness is solely dependent on the patient's motivation [21]. The study by Eroglu et al [11] recorded a statistically significant decrease of plaque level accumulation for all groups (VFR group and FR group) from the initial measurement that was taken after debonding to the last one taken at 13 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent qualitative studies have used interviews to explore young people’s experiences of orthodontic retention in more depth ( Al Moghrabi et al, 2019 ; Frawley et al, 2022 ). The first study found the perceived importance of maintaining tooth position resulted in good short-term adherence; however, longer-term adherence reduced as inconvenience and pragmatic issues associated with the retainers were experienced, such as retainer loss, breakage, issues with cleaning and forgetting retainers ( Al Moghrabi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Facilitators to retainer wear included being shown examples of relapse, support from friends and family, follow-up with the orthodontist and getting into good habits of wearing and maintaining their retainers. The second study found retainers were generally perceived to be easier than active orthodontic appliances and most young people adapted to them easily ( Frawley at al., 2022 ). Factors promoting retainer wear included fear of relapse, not wishing to waste resources through wasted effort if the teeth move and their relationship with the orthodontist.…”
Section: Introductionmentioning
confidence: 99%